Critical Success Factors for BUMDes: Case Study In Magelang Regency - Alya Lutfitasari; Sri Mulyani (Journal of Accounting Auditing and Business, 2022)
BUMDes is social entrepreneurship owned by the village with the primary capital from allocating village funds, intending to manage the village's potential to gain profits and provide social benefits for the village community. This study aims to examine the effect of human resources, community participation, government participation, acceptance of technology, organizational culture, and business feasibility on the success of BUMDes in the Magelang Regency. The BUMDes studied were 151 BUMDes in Magelang Regency using the survey method. The results showed that factors other than human resources had a significant effect on the success of BUMDes in the Magelang Regency. In contrast, the human resource factor has no significant impact on the success of BUMDes in the Magelang Regency